Cephalometric outcomes of a new orthopaedic appliance for Class III malocclusion treatment. (17th June 2019) - Martina, Roberto; D'Antò, Vincenzo; De Simone, Vittoria; Galeotti, Angela; Rongo, Roberto; Franchi, Lorenzo
Summary: Objective: To evaluate dental and skeletal effects of a new orthopaedic appliance for the treatment of Class III malocclusion in growing patients. Material and methods: This retrospective cephalometric study was performed on a sample of 18 patients with a skeletal Class III malocclusion (4 males; 14 females; mean age 8.8 ± 1.5 years) treated with the Pushing Splints 3 (PS3) protocol. The control group consisted of 18 subjects (5 males; 13 females; mean age 9.1 ± 1.8 years) selected from a database of subjects with untreated Class III malocclusion. The cephalometric analysis was performed at the beginning (T0) and the end of the orthopaedic therapy (T1). Significant differences between the treated and control groups were assessed with independent samples t -test ( P < 0.05). Results: In the PS3 group, the post-treatment cephalometric values showed a forward displacement of the maxilla, resulting in a statistically significant increase of the SNA angle. ANPg and Wits appraisal improved significantly compared with the control group. Lingual inclination of mandibular incisors and buccal inclination of the upper incisors were significantly increased in comparison with the control group. No significant differences were recorded for backward mandibular rotation. Limitations: This study presents a short-term evaluation of the treatment and the use of a historical control group. Conclusions: The PS3 was effective for the treatment of Class III malocclusion in growing patients, with favourable maxillary advancement and control of the vertical skeletal relationships.